Pgp-mediated interaction between (R)-[11C]verapamil and tariquidar at the human blood-brain barrier: a comparison with rat data - Bauer, M; Zeitlinger, M; Karch, R; Matzneller, P; Stanek, J; Jäger, W; Böhmdorfer, M; Wadsak, W; Mitterhauser, M; Bankstahl, J P; Löscher, W; Koepp, M; et al. (Clinical pharmacology and therapeutics, 2012)
Using positron emission tomography (PET) imaging we assessed, in vivo, the interaction between a microdose of (R)-[(11)C]verapamil (a P-glycoprotein (Pgp) substrate) and escalating doses of the Pgp inhibitor tariquidar (3, 4, 6, and 8 mg/kg) at the blood-brain barrier (BBB) in healthy human subjects. We compared the dose-response relationship of tariquidar in humans with data obtained in rats using a similar methodology. Tariquidar was equipotent in humans and rats in its effect of increasing (R)-[(11)C]verapamil brain uptake (expressed as whole-brain volume of distribution (V(T))), with very similar half-maximum-effect concentrations. Both in humans and in rats, brain V(T) approached plateau levels at plasma tariquidar concentrations >1,000 ng/ml. However, Pgp inhibition in humans led to only a 2.7-fold increase in brain V(T) relative to baseline scans (before administration of tariquidar) as compared with 11.0-fold in rats. The results of this translational study add to the accumulating evidence that there are marked species-dependent differences in Pgp expression and functionality at the BBB.